Monte Carlo Timeseries Fit Optimization - Gavin Piccione (Zenodo, 2022)
TheseMatlab codes usea Monte Carlo simulation to calculate an optimized age model for subglacial precipitate sampleswithin their individualage uncertainty bounds. They then calculatethe fit between the age model and a user-defined climatethreshold. Relevant data are provided. These codes were used to run the calculations from the manuscript: Subglacial Precipitates Record Antarctic Ice Sheet Response to Pleistocene Millennial Climate Cyclesby Piccione et al. 2022, published in Nature Communications. All codes require a Matlab license. Codes were tested on Matlab version R2021a.